Ustekinumab levels in pregnant women with inflammatory bowel disease and infants exposed in utero. Issue 6 (14th December 2021) - Flanagan, Emma; Prentice, Ralley; Wright, Emily K.; Gibson, Peter R.; Ross, Alyson L.; Begun, Jakob; Sparrow, Miles P.; Goldberg, Rimma; Rosella, Ourania; Burns, Megan; Kiburg, Katerina V.; Bell, Sally J.
Summary: Background: Ustekinumab is increasingly used in pregnant women with inflammatory bowel disease (IBD). Existing safety data are reassuring, but the stability of ustekinumab levels in pregnancy, degree of transfer to the infant and time to infant clearance are unknown. Methods: In this prospective observational study, ustekinumab‐exposed women with IBD had trough levels measured in each trimester of pregnancy and at delivery. Infant ustekinumab levels were measured at delivery and ongoing until clearance was achieved. Trough ustekinumab level stability in individuals across pregnancy was compared by Skillings‐Mack test. Spearman coefficients were used to correlate maternal and infant delivery levels, and median time to infant ustekinumab clearance was defined. Results: 19 pregnant women receiving ustekinumab were included. There was no difference in ustekinumab levels across pregnancy in those with two or more representative trough levels ( P  = 0.83, n = 11). Infant delivery ustekinumab levels were higher than maternal levels, with a median infant:maternal ratio of 1.79 (IQR 1.26‐3.1). There was a positive correlation between maternal and infant delivery ustekinumab levels ( r  = 0.75, P  = 0.001) and an inverse correlation between the number of days from final antenatal dose and delivery infant ustekinumab level ( r  = −0.65, P  = 0.006). Median time of infant ustekinumab clearance was 9 (range 6‐19) weeks (n = 9). Conclusion: Ustekinumab drug levels appear stable in pregnancy, with a delivery infant:maternal ratio similar to that of anti‐TNFs. Infant ustekinumab clearance was complete by 20 weeks post‐partum, however, infants exposed in utero should avoid live vaccination before 12 months of age until further clearance data are obtained. Abstract : Ustekinumab levels are stable over the course of pregnancy, with delivery levels being higher in mothers than infants (ratio 1.8) and a maximal time to clearance of 19 weeks.